College Chemistry II (CH 122) - Ommidala Pattawong (Linn-Benton Community College, 2021)
A remix of several OER chemistry textbooks customized for use at LBCC. Note that some chapters have a more open license. The second of a three term college chemistry sequence for students in human performance, certain health occupations programs, agriculture, animal science, and fisheries and wildlife. This sequence is for students who have had no previous training in chemistry and whose program of study requires only a one-year sequence of college chemistry. Topics include atomic structure, periodic trends, covalent and ionic bonding, atomic and molecular orbital theory, phase changes, colligative properties, intermolecular forces, and organic chemistry.